Sistem Dinamik Ujian Nasional Berbasis Komputer Untuk Meminimalkan Resiko Kecurangan Serta Meningkatkan Efektifitas Dan Efisiensi Anggaran - Rachman Arief; Erma Suryani (INTEGER: Journal of Information Technology, 2016)
The Ministry of Education Indonesia held a national examination for high school students every year with the aim of assessing the achievement of competency standards on specific subjects nationally and as the basis of selection into the next education level. Fraud in paper-basedÂ  implementation of National Examination often found, although it can not be completely eliminated but it can be minimized. National Exam-based computer is one of the policies that can be used to reduce the risk of fraud or violations committed by students, teacher, schools and others who intentionally used for a particular purpose. National Exam-based computer will also improve the effectiveness and efficiency of the budget, because it does not use paper media that will be replaced with computer media and its oversight will be easier. In this research scenario will be simulated implementation of National Examination using a computer-based modeling of dynamic systems. Hopefully, through modeling of dynamic systems can be known factors that cause fraud or breach, as well as a variable in the National Exam that can be analyzed to improve the effectiveness and efficiency of the budget, so the goal of the National Examination can be achieved in order to improve the quality of education in Indonesia.